1968
DOI: 10.1017/s0022112068002417
|View full text |Cite
|
Sign up to set email alerts
|

An analytical and experimental investigation of the velocities of particles entrained by the gas flow in nozzles

Abstract: Among the parameters which determine the erosion damage sustained by the walls of a nozzle, in which a mixture of gas and particles is flowing is the speed attained by the particle before collision with the wall surface. This work is concerned with the determination of the particle velocity, and a number of relationships are given from which the variation in particle velocity can be obtained for a variety of gas conditions. The changes of state and velocity of the gas, occasioned by the interchange of heat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…The difference between actual diameters and equivalent wear diameter should be taken into account when discussing erosion rates based on a mean particle diameter. Neilson and Gilchrist, 1968 showed that the erosion mainly depends on the wall material, the particle velocity, and the angle of attack. In this model, it is assumed that erosion is mainly controlled by particle impingement against the pipe wall.…”
Section: Particle Impingementmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between actual diameters and equivalent wear diameter should be taken into account when discussing erosion rates based on a mean particle diameter. Neilson and Gilchrist, 1968 showed that the erosion mainly depends on the wall material, the particle velocity, and the angle of attack. In this model, it is assumed that erosion is mainly controlled by particle impingement against the pipe wall.…”
Section: Particle Impingementmentioning
confidence: 99%
“…Further, it is assumed that there are no particle-particle interactions within the slurry flow field. Neilson and Gilchrist, 1968 showed that the erosion coefficient, ξ erosion , mainly depends on the incident particle speed, v in , particle size, d p , and the incident angle, β in , which is the angle between a plane tangent to the surface at the impact and the direction of motion of the incident particle. The form of the empirical relation used for the present erosion model is, Designing a scaled erosion test with CFD methods Page 6 of 10 WSRC-MS-2001-00500…”
Section: Particle Impingementmentioning
confidence: 99%
“…Others (7,8) have assumed that aerodynamic drag is responsible for particle motion but that there is no effect of the particle motion on the gas flow. Others (7,8) have assumed that aerodynamic drag is responsible for particle motion but that there is no effect of the particle motion on the gas flow.…”
Section: Theoretical Analysis and Model Equationsmentioning
confidence: 99%
“…Examples include dust ingestion in turbomachinery [ 1,2], solid propellant motion in rocket nozzles [3], raindrop impingement on aircraft surfaces [4], and pulverized coal combustion [5]. In each of these examples and in many others, the particles governing differential equations (namely Newton's second law) are integrated in time over small steps.…”
mentioning
confidence: 99%